2020
DOI: 10.1186/s12891-020-3154-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the role of inflammatory biomarkers in acute, subacute and chronic non-specific low back pain

Abstract: Background: Low back pain (LBP) is one of the greatest contributors to disability in the world and there is growing interest on the role of biomarkers in LBP. To purpose of this review was to analyze available evidence on the relationship between inflammatory biomarkers, clinical presentation, and outcomes in patients with acute, subacute and chronic non-specific low back pain (NSLBP). Methods: A search was performed in Medline, Embase, Cinahl and Amed databases. Studies which measured levels of inflammatory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 34 publications
3
68
1
Order By: Relevance
“…Our post hoc analysis showed significantly increased circulating TNF-α in fibromyalgia patients, only after the exclusion of two outlier studies, which was robust on sensitivity analysis. In support of our findings, a recent systematic review of biomarkers associated with chronic non-specific back pain also identified two studies that reported increased levels of circulating TNF-α [ 52 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our post hoc analysis showed significantly increased circulating TNF-α in fibromyalgia patients, only after the exclusion of two outlier studies, which was robust on sensitivity analysis. In support of our findings, a recent systematic review of biomarkers associated with chronic non-specific back pain also identified two studies that reported increased levels of circulating TNF-α [ 52 ].…”
Section: Discussionsupporting
confidence: 88%
“…Biomarkers are key to the pursuit of stratifying disease progression and prognosis in chronic back pain. To date, primary areas of foci often require minimally-invasive procedures (e.g., blood-based markers) to examine genetic or pro-inflammatory cytokine associations with pain severity, with mixed diagnostic success 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In the past, several putative non-imaging biomarkers have been investigated in LBP (5)(6)(7). However, these biomarkers are often invasive and do not assess the impact of LBP on the brain.…”
Section: Introductionmentioning
confidence: 99%